Catalog of the types of Coleoptera (Insecta) deposited at Museo de Historia Natural de la Universidad Nacional Mayor de San Marcos (MUSM), Lima, Peru - Asenjo, Angélico; Figueroa, Luis (Zootaxa, 2017)
The Coleoptera type species of Museo de Historia Natural de la Universidad Nacional Mayor de San Marcos housed in the Entomology Department, Lima, Peru, were examined and listed. This is an important collection in South America and the largest in Peru. All type material of Coleoptera were studied and photographed. Complete information is given for each type specimen, including the reference of the original description and labels data. A total of 275 types specimens were listed and arranged in families.